THE INFLUENCE OF FAMILY’S ENVIRONMENT, MOTIVATION AND PERCEPTION OF UNIVERSITY STUDENT ABOUT THE PROFESSION OF PUBLIC ACCOUNTANT AGAINST THE INTENTION TO BE PUBLIC ACCOUNTANT TO ACCOUNTING STUDENT IN BENGKULU CITY - Pandu Chaniago; Fitrawati Ilyas (Jurnal Akuntansi, 2017)
The aims of the study were: (1) to analyze the influence of family’s environment against the intention to be public accountant to accounting student; (2) to analyze the motivation against the intention to be public accountant to accounting student; and (3) to analyze the perception of student about public accountant against the intention to be public accountant to accounting student. In this research use Theory of Planned Behavior. The used data was primary data obtained by spreading questionnaires to accounting students of VII semester of economics faculty city of Bengkulu. The total of sample used in this study was 76 respondents. The method of analyzing the data applied was multiple linear regressions.From hypothesis testing it was gotten the result that: (1) family’s environment has a significant influence against the intention to be public accountant to accounting student; (2) Motivation has a significant influence against the intention to be public accountant to accounting student; and (3) student perception about the profession of public accountant has a significant influence toward the intention to be public accountant to the accounting student.Key words: Family’s Environment, Motivation, Perception, Intention and Public Accountant